RESPONSE OF MULTI CUT FODDER SORGHUM WITH THE APPLICATION OF SOURCES OF IRRIGATION AND NUTRIENTS - C. Vennila; T. Ananthi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Multicut fodder sorghum Co (FS) 29 was evaluated for its growth and yield performance with the application of different sources of irrigation and nutrients. The experiment was conducted in split plot design with three replications. Main plot consists of treatments with application of irrigation through ground water (I1), domestic sewage water (I2) and ground and domestic sewage water alternatively (I3). The sub plots consist of no fertilisers (control) (N1), application of farm yard manure alone (FYM alone) (N2), farmyard manure + NPK (FYM + NPK) (N3) and NPK alone (N4). The application of domestic sewage water along with FYM + NPK nutrients as per the treatment schedule resulted in higher plant height, leaf length, number of leaves, biomass production, dry matter and biomass yield of multicut fodder sorghum. However, pertaining to nutrient application, nitrogen uptake was higher with application of FYM +NPK but found on par with the application of NPK alone and application of FYM alone.